Case study on the performance evaluation of the MASkargo agents at Madras, India / Nur Izzati Ab. Rahman - Ab. Rahman, Nur Izzati (Faculty of Business and Management, 2010)
This studies was conducted for the purposed of to determine the process involved in appointing ground handling agents and to study on the performance evaluation of the MASkargo agents at Madras, India. This is involved by two agents, Air-India Limited and Esquire Express India Private Limited (Chennai). It is also to evaluate the process standardization positively impacts on the process performance of agent. The main objective of this study was to minimize the problem of agents in ground handling services at MASkargo. Even though MASkargo have follows the procedures before selecting the right agents, but the agents does not reach the company target of services and performance. The problems that usually occur such as operational analysis and many types of mishandled. It is worth to study the problems to find the ways to minimize the mishandled and suggest the elements needed for the company to make their agents successful.